Ex vivo evaluation of reduced myocardial beta-adrenergic receptor binding in the streptozotocin-treated hyperglycaemic rats using (S)-[(3)H]CGP12177 - Parsa-Nezhad, Maryam (University of Ottawa (Canada), 2008)
Type II Diabetes Mellitus (DM) is a common metabolic disorder that affects millions of people worldwide. Elevated blood glucose levels in type II DM is associated with altered sympathetic nervous system (SNS) activity and enhanced noradrenaline (NA). Persistent NA release, in turn, leads to alterations in beta-adrenergic receptor (betaAR) density and downstream signalling. A common complication of diabetes is cardiovascular disease. In this project, myocardial betaAR density was evaluated in hyperglycaemic streptozotocin (STZ)-treated rats fed high fat diet (HFD), using betaAR antagonist (S)-[3H]CGP12177. At 30 minutes post injection, the radiotracer exhibited specific binding in myocardial regions, brown adipose tissue and kidney, and was capable of measuring reduced binding to betaARs. A subset of HFD moderate-STZ treated rats became hyperglycaemia, whereas the remainder maintained euglycaemia. At 10 days post-STZ, no alteration was observed in tracer binding in either sub-group. At 56 days, hyperglycaemic rats displayed a significant reduction in specific binding to betaARs in myocardial regions (30-40%), while no alteration was observed in euglycaemics or controls. This finding suggests a strong association between sustained hyperglycaemia and alterations in SNS activity and PAR binding.
Keywords: Biology, Molecular.